2021
DOI: 10.1108/jme-05-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

An examination of educator multicultural attitudes before and after a diversity dinner dialogue

Abstract: Purpose The demographic make-up of students in US public schools is becoming increasingly diverse, and a need exists to train teachers in multicultural competence. Despite this need, little research addresses multicultural competence training for in-service teachers. In this pilot study, we aimed to implement an intervention, known as a diversity dinner dialogue (DDD), in which elementary and university educators read the same diversity-related book, then gathered over dinner to discuss the book and its implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…En un estudio realizado en los EUA se comprobó que los participantes respondían positivamente a las denominadas DDD ( diversity, dinner, dialogue ), es decir, diversidad, diálogo y comidas; sin embargo, las relaciones multiculturales decaían después de la formación, lo que podría ser un signo de que los participantes afrontaban procesos de desarrollo de su identidad racial durante la intervención (tras leer el libro señalado; Merlin-Knoblich & Dameron, 2020).…”
Section: Estrategias De Resolución De Conflictos En Entornos Educativ...unclassified
See 1 more Smart Citation
“…En un estudio realizado en los EUA se comprobó que los participantes respondían positivamente a las denominadas DDD ( diversity, dinner, dialogue ), es decir, diversidad, diálogo y comidas; sin embargo, las relaciones multiculturales decaían después de la formación, lo que podría ser un signo de que los participantes afrontaban procesos de desarrollo de su identidad racial durante la intervención (tras leer el libro señalado; Merlin-Knoblich & Dameron, 2020).…”
Section: Estrategias De Resolución De Conflictos En Entornos Educativ...unclassified
“…A study conducted in the USA found that participants positively responded to DDD (diversity dinner dialogue); however, multicultural relations declined after training, which is a potential sign that participants faced racial identity development processes during the intervention (after reading the book; Merlin-Knoblich & Dameron, 2020).…”
Section: The Situation In the Russian Federation And In The Worldmentioning
confidence: 99%
“…A Diversity Dinner Dialogue (DDD) is a school‐wide prejudice reduction intervention that school counselors can implement to promote positive MC attitudes (Merlin‐Knoblich et al., 2021; Merlin‐Knoblich & Dameron, 2021). In a DDD, participants read the same diversity‐related book and then gather together over dinner to discuss their reactions to the book and its implications for their community (Merlin‐Knoblich et al., 2021; Merlin‐Knoblich & Dameron, 2021). In this case study, we researched participants in a DDD led by professional school counselors and held with students and faculty at a suburban high school.…”
Section: Professional School Counselors and MC Interventionsmentioning
confidence: 99%
“…A Diversity Dinner Dialogue (DDD) is a school-wide prejudice reduction intervention that school counselors can implement to promote positive MC attitudes Merlin-Knoblich & Dameron, 2021). In a DDD, participants read the same diversity-related book and then gather together over dinner to discuss their reactions to the book and its implications for their community Merlin-Knoblich & Dameron, 2021). In this case study, we researched participants in a DDD led by professional school counselors and held with students and faculty at a suburban high school.…”
Section: Professional School Counselors and MC Interventionsmentioning
confidence: 99%